SINGAPORE’S SCHOOL EXCELLENCE MODEL AND HONG KONG’S SCHOOL-BASED MANAGEMENT - Fadlia Fadlia Fadlia (Program Studi Pendidikan Sejarah - Universitas Samudra, 2017)
This paper aims to elaborate and compare the school excellence model (SEM) approach adopted by Singapore and the school-based management (SBM) approach adopted by Hong Kong. It discusses the impact those educational strategies and the challenges that both Singapore and Hong Kong schools face in implementing the new form of managerialism while fulfilling the requirements of quality assurance. This paper utilizes a comparative approach to analyze both of two educational policies through literature research. The analysis are included approach to decentralization; effects of education marketization; school leaders, teachers and the profitable use of quality models. The literature research has revealed that both Singapore and Hong Kong utilize a centralized decentralization approach though with different intent. The comparative study of Singapore and Hong Kong serves the new horizon to other developing countries in understanding how the educational policies that stressed on quality framework, self-assessment and external supervision can lead to changes in the school system both positive ones and the drawback itself.